Gender and age group-wise inequality in health burden and value of premature death from COVID-19 in India - Chandan Kumar Swain; Himanshu Sekhar Rout (Aging and Health Research, 2023)
Background: Earlier studies have focused on the age-group-wise health burden of COVID-19 while few studies have focused on the gender-wise analysis of the burden of COVID-19. The present study estimated the health burden and value of premature mortality from COVID-19 based on gender and age. Methods: This study was based on secondary data collected from several sources of the government of India. To quantify the health burden, the disability-adjusted life years (DALY) method was used. An abridged life table was used to estimate the fall in life expectancy due to COVID-19. The value of premature mortality was estimated by using the human capital approach. Results: Among COVID-19 cases, 65.08% were males and 34.92% were females. The overall health burden caused by COVID-19 was 19,24,107 DALY in 2020, 43,40,526 DALY in 2021, and 8,08,124 DALY in 2022. The health burden per 1000 males was more than double that per 1000 females. This was due to higher rates of infection and case fatality rate among males compared to females. The age group 60–64 years experienced the highest loss of healthy life years per 1000 people, while the age group 55–59 years had the highest overall loss. Due to additional deaths from COVID-19, life expectancy decreased by 0.24 years in 2020, 0.47 years in 2021, and 0.07 years in 2022. The total value of premature death in the first three years of the COVID-19 pandemic amounted to 15,849.99 crores INR. Conclusion: In India, males and the older population were more susceptible to the impact of COVID-19.